The energy cost of polypeptide knot formation and its folding consequences - Andrés Bustamante (Nature Portfolio, 2017)
The effect of knots on protein stability and folding kinetics is not well understood. Here the authors combine optical tweezer experiments and calculations to experimentally determine the energy cost for knot formation, which indicates that knotted proteins evolved specific folding pathways because knot formation in unfolded chains is unfavorable.